The Effect of Deactivating Groups in the Formation of Some Biologically Important Lactams (Isatins) and their Further Derivatization (Journal of the Bangladesh Chemical Society, 2012)
Treatment of different aromatic primary amines (7a-b) with chloral hydrate andhydroxylamine hydrochloride under microwave (MW) conditions afforded correspondingisonitrosoacetanilides (6a-b). These intermediate compounds (6a-b) were cyclized inconc. H2SO4 medium to give cyclic amides (5a-b) by means of elcetrophilicaromatic substitution reaction. The microwave (MW) mediated treatment of compound5a with thiosemicarbazide afforded the corresponding Schiff-base 4a, which undergoescyclization to give thiadiazoline (1). Beside, compound 4a was also treated with aq KOHsolution under MW condition to give triazinothione (3). The Sn-HCl mediatedreduction of compound 3 afforded the corresponding 6-aminothione (2). On the otherhand, compound 5b was treated with o-phenylenediamine under MW condition to givethe corresponding quinoxaline derivative 4b in excellent yield. DOI: http://dx.doi.org/10.3329/jbcs.v25i1.11771 Journal of Bangladesh Chemical Society, Vol. 25(1), 46-52, 2012